Triging Student Learning Results with Utilizing Google Classroom and Zoom Platform - I Wayan Eka Mahendra (Jurnal Ilmiah Sekolah Dasar, 2021)
During the pandemic, online learning has been carried out almost all over the world, making it mandatory for teachers to have skills in creating fun online learning for students. Teachers still find it challenging to choose an online learning platform that can facilitate students ' learning. This study aims to analyze the differences in student science learning outcomes between students who take online learning using a combination of google classroom and zoom and students who take online learning with the WA group. This study involved a sample of 92 students who were taken by a simple random sampling technique. Data on students' science learning outcomes were collected using tests that had previously been tested for content validity, empirical validity, and reliability coefficients. The collected data were analyzed using one-way covariance analysis by first testing the normality of the data distribution, the linearity of the regression line, and the homogeneity of variance. The results of this study indicate differences in science learning outcomes between students who take online learning a combination of google classroom and zoom with students who take online learning with WA group after controlling for the initial knowledge variable with an average learning outcome of 73.17 and 58.76. It can be concluded that students who take online learning a combination of google classroom and zoom can improve student learning outcomes. This research implies that teachers can use google classroom and zoom as platforms for online learning.